Microstructure: Surface and cross-sectional studies of hydroxyapatite formation on the surface of white Portland cement paste in vitro - Arnon Chaipanich (2018)
The formation of hydroxyapatite was investigated at the surface and at the cross-section of white Portland cement paste samples before and after immersion in simulated body fluid. Scanning electron microscope images showed that hydroxyapatite were found at the surface of white Portland cement after immersion in simulated body fluid. Hydroxyapatite grains of mostly ≈1 μm size with some grain size of ≈2-3 μm were seen after 4 days immersion period. More estabilshed hydroxyapatite grain size of ≈3 μm grains were observed at longer period of immersion at 7 and 10 days. The cross-section of the samples was investigated using line scanning technique and was used to determine the hydroxyapatite layer. A strong spectrum of phosphorus is detected up to 6-8 μm depth for samples after 4, 7 and 10 days immersion in simulated body fluid when compared to weak spectrum detected before immersion. The increase in the phosphorus spectrum corresponds to the hydroxyapatite formation on the surface of the samples after the samples were placed in simulated body fluid. © 2011 Elsevier B.V. All rights reserved.